Targeting Phosphatidylserine Enhances the Anti-tumor Response to Tumor-Directed Radiation Therapy in a Preclinical Model of Melanoma - Budhu, Sadna; Giese, Rachel; Gupta, Aditi; Fitzgerald, Kelly; Zappasodi, Roberta; Schad, Sara; Hirschhorn, Daniel; Campesato, Luis Felipe; De Henau, Olivier; Gigoux, Mathieu; Liu, Cailian; Mazo, Gregory; et al. (Cell reports (Cambridge), 2021)
Phosphatidylserine (PS) is exposed on the surface of apoptotic cells and is known to promote immunosuppressive signals in the tumor microenvironment (TME). Antibodies that block PS interaction with its receptors have been shown to repolarize the TME into a proinflammatory state. Radiation therapy (RT) is an effective focal treatment of isolated solid tumors but is less effective at controlling metastatic cancers. We found that tumor-directed RT caused an increase in expression of PS on the surface of viable immune infiltrates in mouse B16 melanoma. We hypothesize that PS expression on immune cells may provide negative feedback to immune cells in the TME. Treatment with an antibody that targets PS (mch1N11) enhanced the anti-tumor efficacy of tumor-directed RT and improved overall survival. This combination led to an increase in proinflammatory tumor-associated macrophages. The addition of anti-PD-1 to RT and mch1N11 led to even greater anti-tumor efficacy and overall survival. We found increased PS expression on several immune subsets in the blood of patients with metastatic melanoma after receiving tumor-directed RT. These findings highlight the potential of combining PS targeting with RT and PD-1 pathway blockade to improve outcomes in patients with advanced-stage cancers. [Display omitted] •PS expression on immune cells in murine melanoma is increased after tumor-directed RT•Blocking PS interaction with its receptors enhances the anti-tumor efficacy of RT•PD-1 blockade further potentiates the anti-tumor responses•Melanoma patients’ PBMCs exhibit an increase in PS expression after RT Budhu et al. show that tumor-directed irradiation of murine B16 melanoma causes an increase in PS on the surface of infiltrating immune cells. Blocking PS and RT improves the anti-tumor efficacy and overall survival, which can be further improved with the addition of anti-PD-1. Melanoma patients exhibit increased PS on their PBMCs after RT.